2002
DOI: 10.1002/jcop.10016
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring relationships for youth: Investigation of a process‐oriented model

Abstract: Ⅲ We investigated a process-oriented model of mentoring using data on 50 relationships in a Big

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(173 citation statements)
references
References 15 publications
9
161
2
1
Order By: Relevance
“…Youth in MRs classified as high in quality experienced a reduced chance of an early closure compared to those in low to moderate quality relationships. This result highlights the importance of quality in maintaining relationship continuity and corresponds to earlier research identifying relationship quality as a strong positive correlate of MR longevity (Parra, DuBois, Neville, Pugh-Lilly & Povinelli, 2002;Rhodes et al, 2005). The result is also important in that it is based on an assessment of relationship quality that includes the perspective of parents.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Youth in MRs classified as high in quality experienced a reduced chance of an early closure compared to those in low to moderate quality relationships. This result highlights the importance of quality in maintaining relationship continuity and corresponds to earlier research identifying relationship quality as a strong positive correlate of MR longevity (Parra, DuBois, Neville, Pugh-Lilly & Povinelli, 2002;Rhodes et al, 2005). The result is also important in that it is based on an assessment of relationship quality that includes the perspective of parents.…”
Section: Discussionsupporting
confidence: 82%
“…This finding challenges the notion that level of contact by itself may not be sufficient for sustaining MRs but instead provides the context for meaningful interactions between mentees and mentors to grow (Parra et al, 2002). It is possible that regardless of relationship quality, weekly contact reflects an underlying commitment to relationship development or allows for regular structured activities that have the effect of prolonging the MR for extended periods.…”
Section: Discussionmentioning
confidence: 76%
“…Special attention has been paid to the characteristics of the students targeted by specific programs (e.g., level and kind of risk), the characteristics of the mentors (e.g., perceived self-efficacy), and the characteristics of the program (e.g., presence of monitoring) that may potentially moderate the impact of the mentoring relationship. Before describing these different aspects, it is perhaps noteworthy to underline that in their metaanalytic review, DuBois, Neville, Parra, and Pugh-Lilly (2002) found evidence that the effects of mentoring programs on youth adjustment are moderated by the kind of setting that provides the context for mentoring activities. When mentoring activities were set in schools, the estimated impact of mentoring relationships was substantially lower than that of programs set in the workplace or the community, suggesting that community-based models of mentoring do not readily transfer to school settings.…”
Section: Academically At-risk Studentsmentioning
confidence: 98%
“…Procedures, such as factor analysis and cluster analysis, are well suited to the task of identifying salient dimensions or typologies of mentoring relationships (Sipe, in press), for example, but have been employed only to a limited extent (e.g., Darling, Hamilton, Toyokawa, & Matsuda, 2002;Langhout, Rhodes, & Osborne, 2004;Liang, Tracy, Taylor, & Williams, 2002). Similarly, structural equation modeling provides a valuable, but underutilized technique for testing theories of mentoring and its effects on youth outcomes (e.g., DuBois, Neville, Parra et al, 2002;Rhodes, Grossman, & Resch, 2000).…”
Section: Basic Researchmentioning
confidence: 98%